Prevalence and clinical predictors of fibromyalgia in patients with rheumatoid arthritis - Deb, Aparna; Sultan, Mohammad Imtiaz; Islam, Mohammed Taherul; Arif, M. Saiful; Dey, Protyay; Saha, Mrinal; Begum, Rayhana; Dhar, Sangita; Tabassum, Tamanna; Kabir, Sayeema (International Journal of Research in Medical Sciences, 2026)
Background: Fibromyalgia (FM) is a common disorder in patients with rheumatoid arthritis (RA) and contributes to the inflation of disease activity scores because of a high symptom similarity. Objective of the study was to estimate the prevalence of FM in patients with RA and to identify clinical predictors. Methods: A total of 150 RA patients were enrolled in this cross-sectional study. FM status was determined by WPI and SSS. Sociodemographic, clinical, laboratory and disease activity parameters were evaluated. Results: The prevalence of fibromyalgia in patients with RA was 24%. The participants had a mean age of 52.02±12.13 years and were predominantly female at an 81.3% rate. Patients with both RA and FM presented with more swollen joint count, higher patient VAS scores, DAS28 scores, CDAI scores and SDAI compared to those without FM. Depression and fatigue were more common in FM-positive patients. Conclusions: Nearly one fourth of patients with RA had FM diagnosed concurrently. Psychological and subjective disease components were strongly correlated with FM in this study, indicating that higher disease activity scores may not always represent an active inflammation.